The Berenstain Bears and the nerdy nephew - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1993)
Brother and Sister Bear don't realize the problems they will face when they agree to help Professor Actual Factual's super-smart nephew fit in at school.
560
560
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; Behavior -- Juvenile fiction; Bears -- Juvenile fiction